Clinical study of tubectomy and it’s complications - Abdul Aziz, Fasiha T.; R., Kruthi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Tubectomy is most accepted method of contraception in India. Female sterilization may be performed in several ways such as abdominal tubal ligation, laparoscopic and hysteroscopic methods. Although considered as minor and safe procedure, complications leading to even death have been reported. So, this study was taken up to study complications of different types of tubal ligation. Objective of this study was to study complications of different types of tubal ligation. Methods: This is a prospective analytical study over the period of 18 months. This study includes all cases that have reported or referred as female sterilization complication. Results: At study institute both laparoscopic tubal ligation (TL) and abdominal tubal ligation are done. During the period of 18 months, 50 cases of tubectomy complications were noted at our institute, out of 40 cases (80%) were of abdominal method and rest 10 (20%) were of laparoscopic method. In 33 cases (66%) sterilization was performed at primary health centre. 3 cases of death reported in this study. Conclusions: At study institute both laparoscopic tubal ligation (TL) and abdominal tubal ligation are done. During the period of 18 months, 50 cases of tubectomy complications were noted at our institute, out of 40 cases (80%) were of abdominal method and rest 10 (20%) were of laparoscopic method. In 33 cases (66%) sterilization was performed at primary health centre. 3 cases of death reported in this study.